PENILAIAN DATA AWAL PENERAPAN BRIEF CONSELING FARMASIS DALAM PENINGKATAN PERILAKU, KEPATUHAN MINUM OBAT, HASIL TERAPI DAN KUALITAS HIDUP PASIEN HIPERTENSI DI RSUD ULIN BANJARMASIN - Saftia Aryzki; Amaliyah Wahyuni (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Hypertension is one of the deadliest diseases in the world. As many as 1 billion people in the world or 1 in 4 adults suffer from this disease.In fact, it is estimated that the number of hypertension sufferers will increase to 1.6 billion by 2025. Based on data from Basic Health Research (Riskesdas) in 2018, the prevalence of hypertension is based on measurement results for people aged ≥ 18 years in South Kalimantan, ranking number 1 in Indonesia. This result increased from the data in 2013 the prevalence of hypertension was 30.4% to 44.1%. Patient behavior by controlling the patient's blood pressure will improve the patient's quality of life. The purpose of this study was to assess the initial data on the application of the effect of pharmacist brief counseling in improving behavior, medication adherence, therapy outcomes and quality of life for hypertensive patients at Ulin Banjarmasin Hospital. The study was a quasi-experimental study using two groups with prospective patient data collection with inclusion and exclusion criteria. The exclusion criteria were pregnant, deaf and absent patients at the second visit. Data collection comes from medical records and is carried out by interviewing then filling out a questionnaire. Data were analyzed using SPSS Version 16. The results of the study were on cognitive (0.408), affective (0.000), psychomotor (0.240) patient behavior; compliance (0.096); quality of life (0,000); Systolic BP (0.588) and Diastolic BP (0.626).